"X-rays" of self and society : Dambudzo Marechera's avant-gardism and its implications for debates concerning Zimbabwean literature and culture - Shaw, Drew Campbell (Department of English Language and Literature, 2016)
This thesis discusses Dambudzo Marechera's avant-gardism and its significance in the context of Zimbabwean literature and culture. I use the term avant-garde to describe Marechera's defiance of hegemonies, traditions, and prescriptions for writing, as well as his innovations with form and style. In the context of Zimbabwe, Marechera's avant-gardism involves a rejection of cultural nationalism, and an eschewal of traditional realist criteria for writing. The thesis locates Marechera in a socio-historical context, and in the framework of black Zimbabwean literature (written in English). It discusses his rejection of the nationalist tradition set by his literary predecessors; and it compares him with his contemporaries, Stanley Nyamfukudza and Charles Mungoshi, who also reject the concept of a 'pure', homogeneous, national culture in their writings. Marechera's writing explores new (and often taboo) subject matter, and it thus illustrates the diverse, complex nature of the Zimbabwean experience. It also abandons the unified, linear narrative; and it has been sharply censured by nationalist critics -- largely on the grounds of its transgression of traditional narrative form. Nationalist critics have tended to privilege traditional realist criteria in their discussions of Zimbabwean literature, and Marechera, as an avant-gardist, has been marginalized and denigrated for his non-conformity. In this thesis, I challenge the privileged status of traditional realism, question the prescriptions of nationalist/realist critics, and attempt to demonstrate the value of Marechera's non-realist writing. While many nationalist critics allege that Marechera's writing is 'unAfrican', I argue that it is a fallacy to assume his work is 'Europeanized' while nationalist/realist writing is not. Moreover, I contend that Marechera's avant-gardism is in direct response to a set of extraordinary socio-historical, political and cultural conditions -- which are specific to Zimbabwe. In analyzing Marechera's alternatives to realism (such as expressionism, stream of consciousness, surrealism, grotesque realism, the carnival, magical realism, and Menippean satire), I maintain that his experiments are not without strategy, but that they address pertinent literary, social, political, and cultural issues. The thesis furthermore attempts to show how the 'individualism' -- for which Marechera has been roundly condemned -- is paradoxically transformed into sharp and poignant social commentary. This is particularly evident in two texts which I focus on: "House of Hunger" -- his irreverent pre-independence vivisection of Zimbabwean society; and Mindblast, his much neglected anti-realist post-independence compilation, which I discuss in some detail.